Thermal inertia of Occator's faculae on Ceres. (1st October 2021) - Rognini, E.; Capria, M.T.; Tosi, F.; De Sanctis, M.C.; Ciarniello, M.; Longobardo, A.; Carrozzo, F.G.; Raponi, A.; Formisano, M.; Frigeri, A.; Palomba, E.; Fonte, S.; et al.
Abstract: Thermal inertia is a key information to quantify the physical status of a planetary surface; it can be retrieved by comparison between theoretical and observed temperature diurnal profiles. We have calculated the surface temperature for a set of locations on Ceres' surface with a thermophysical model that provides temperature as a function of thermal conductivity and roughness, and we have determined the values of those parameters for which the best fit with the observed data is obtained. The observed temperatures have been retrieved form spatially-resolved data from the Dawn mission. In our previous work [ Rognini et al., 2019], we have found that the average thermal inertia for the overall surface of Ceres is low (from 1 to 15 to 60 ​J ​m −2 ​s −½ K −1 ), as expected according to the general trend observed in the Solar System for atmosphere-less bodies, while the thermal inertia of the very bright faculae found in the floor of the Occator crater could not be well defined. Using more recently acquired VIR high resolution data we find that the central part of the Cerealia facula displays a thermal anomaly ( 10 K above the average) compatible with a higher thermal inertia with respect to the surrounding regions, while the Vinalia facula does not display any consequently could have a grain size comparable with the Ceres' surface average. Highlights: New high resolution data revealed a thermal anomaly in the center of Cerealia facula. Higher thermal inertia may be an indicator of higher grain size or cementation. Faculae are not homogeneous, different evolutionary history may be possible.